PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN ASPEK WIRAGA WIRASA DAN WIRAMA - Wisika Jusmawati; Agus Syahrani; Winda Istiandini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe researcher applied the role-playing method to the Ruai bird dance-drama to improve the aspects of the pleasure, expression, and timing of seventh-grade students in SMP Negeri 2 Pontianak. This role-playing method is a method that plays the role of a work. The aim of this research is to describe the process of the method of role playing and the results of the increase in pleasure, expression, and timing after applying this method in the dance-drama of Ruai bird. Research conducted in the form of classroom action research with descriptive methods and qualitative approaches. Theoretical tests conducted in first cycle with the scores obtained by students reached an average of 6.2. In the second cycle there is an increase to 81.94. The improvement is seen from students demonstrating the movement in accordance with their role. In addition, students can also appreciate and express according to the role that has been determined and students are also able to understand the accompaniment of music in accordance with a predetermined theme. Thus, it can be concluded that the application of the role-playing method in the Ruai Bird Dance-drama can increase the aspects of pleasure, expression, and timing of seventh-grade students at class A in SMP Negeri 2, Pontianak. Keywords: Expression, Pleasure, Role-Playing Method, Ruai Bird Dance-drama, and Timing.